Does socket liner material affect clinical outcomes in lower limb prosthesis users? Insights from a randomized control trial. Issue 2 (25th April 2022) - Fiedler, Goeran; Singh, Anita; McKernan, Gina
Abstract : Among the noted disadvantages of prosthesis suspension by flexible liner is the increased rate of perspiration within the socket, which has the potential to cause discomfort, suspension issues, and tissue damage. In recent years, phase change material technology has been adopted for the use in prosthesis liners. These promise to improve temperature control and, consequently, reduce sweating. Previous work has demonstrated that this approach is effective in slowing the temperature increase at the limb-socket interface, but it was not clear how this would translate to clinical outcomes. This study had the aim to compare conventional and phase change material liners regarding prosthesis utilization, physical performance, and patient-reported outcome measures. A randomized double-blind cross-over study design with 6-month intervention periods was used. Of the 42 enrolled participants, only 50% completed the protocol. The high attrition was in large part because of the COVID-19 pandemic that started disrupting daily life and thereby the data collection midway through the study period. The findings indicate that the temperature control liners were, by trend, associated with better prosthesis utilization. The found effects did not reach the level of statistical significance, which is likely a result of the unduly reduced sample size.